Monetary Magic? : How the Fed Improved the Flexibility of the U.S. Economy - Bayoumi, Tamim (IMF Working Papers; Working Paper, 2004)
Extending recent theoretical contributions on sources of inflation inertia, we argue that monetary uncertainty accounts for sluggish expectations adjustment to nominal disturbances. Estimating a model in which rational individuals learn over time about shifts in U.S. monetary policy and the Phillips curve, we find strong evidence that this link exists. These results bring into question the standard approach for evaluating monetary rules by assuming unchanged private sector responses, help clarify the role of monetary stability in reducing output variability in the United States and elsewhere, and tell a subtle and dynamic story of the interaction between monetary policy and the supply side of the economy.